Within‐ and between‐subject consistency of perceptual segmentation in periodic noise: A combined behavioral tapping and EEG study - Ringer, Hanna; Schröger, Erich; Grimm, Sabine (Psychophysiology, 2023)
It is remarkable that human listeners can perceive periodicity in noise, as the isochronous repetition of a particular noise segment is not accompanied by salient physical cues in the acoustic signal. Previous research suggested that listeners rely on short temporally local and idiosyncratic features to perceptually segment periodic noise sequences. The present study sought to test this assumption by disentangling consistency of perceptual segmentation within and between listeners. Presented periodic noise sequences either consisted of seamless repetitions of a 500‐ms segment or of repetitions of a 200‐ms segment that were interleaved with 300‐ms portions of random noise. Both within‐ and between‐subject consistency was stronger for interleaved (compared with seamless) periodic sequences. The increased consistency likely resulted from reduced temporal jitter of potential features used for perceptual segmentation when the recurring segment was shorter and occurred interleaved with random noise. These results support the notion that perceptual segmentation of periodic noise relies on subtle temporally local features. However, the finding that some specific noise sequences were segmented more consistently across listeners than others challenges the assumption that the features are necessarily idiosyncratic. Instead, in some specific noise samples, a preference for certain spectral features is shared between individuals. This study sought to test the assumption that listeners use short idiosyncratic features to segment unstructured, perceptually homogeneous sounds, which was suggested by previous research. Our approach to disentangle variability within and between individuals revealed that, while there is some variability at both levels, a preference for certain features may be shared inter‐individually. The study highlights that separating these two levels provides valuable insights into variability of perceptual processes within and between individuals.